Scandinavian Civil Society and Social Transformations The Case of Norway (Nonprofit and Civil Society Studies, An International Multidisciplinary Series,, 2018)
This book aims at presenting a conceptual apparatus and empirical analysis of the ways Nordic civil society is affected by social transformations by focusing on the Norwegian case. The Norwegian empirical focus allows identifying processes and factors of change that are relevant outside this context and enable us to understand, on a more general basis, the relationship between social transformations and transformations affecting the voluntary sector. This book will make an original contribution to the field of comparative civil society studies both by increasing the available knowledge on the Nordic civil society model and by analyzing the societal transformations affecting civil society over time.